Transformasi Transportasi Tradisional (Offline) ke Transportasi Online Sebagai Solusi Bagi Pengguna di Kota Pontianak - Bustami, Bustami; Laksamana, Rio (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2019)
This study aims to analyze the transforming offline transportation to Online Transportation, seen from the perception of users in the city of Pontianak. This study describes the perceptions of users of transportation services in the city of Pontianak with the Participatory Action Research (PAR) approach. This research concludes that online transportation is the right solution for the community (users) in the city of Pontianak. The community as a user is of the opinion that online transportation which is present in the midst of the bustle of the community with all its advantages (advantages), is the right solution to replace the use of traditional / offline modes of transportation which are felt to be diminished. The advantages of online transportation such as lower prices, easy to use, flexible, time efficient, various services, fast response and good service. In other words, the existence of online transportation has an important role in meeting the daily needs of users of transportation services for the people in Pontianak.